Influence of Different Density Towards Survival Rate and Growth of Red Tilapia (Oreochromis niloticus) In Salty Water Using Recirculation System - Situmorang, Romaida; Mulyadi, Mulyadi; Rusliadi, Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe aim of research was to find out the effect of different densities on the growth and survival rate tilapia fish (Oreochromis niloticus) brackish water using a recirculation system. The research was conducted in 35 days observation, started from March to May 2018 at UPT Teluk Papal Village, Bantan districts, Bengkalis regency, Riau Province. The test fish used are red tilapia fishs (Oreochromis niloticus) that have a measurement of 3 – 5 cm. The method used this research is Completely Randomized Design (CRD), with 5 treatments and 3 replications each. The difference of density of dispersion at each treatment P1, P2, P3, P4 and P5 are 25, 20, 15, 10, dan 5 fishs/10 liters in brackish water with recirculation system. The fish are fed adlibitum at 08.00, 12.00, dan 16.00 WIB. The results showed density did not have effect on survival rate (P> 0,05), but has an effect on absolute weight growth, length total and daily growth rate (P> 0,05). The value of growth and survival rate is the best obtained from 5 fishs /10 liter stocking density treatment with an absolute weight of 6.06 grams, an absolute length of 3.71 cm, a specific growth rate of 5.97% and a 100% survival rate. Keywords: Tilapia, density, growth, survival rate, recirculation systems